An acoustic study on character voices of dominators and subordinates: A case study on male characters in Empresses in the Palace - Liu, Wen; Zhang, Xinyi; Liang, Changwei (Frontiers in Communication, 2023)
Voice has been used to project identity in dubbing, in order to auditorily portray appropriate role images in TV dramas. In this study, taking the character voices of leading male characters in Empresses in the Palace as the research object, different acoustic characteristics of character voices and matching relation between acoustics and images are explored by comparing F0, CPP, harmonic amplitude differences of speech spectrum. We found that the voice quality of characters is related to their relative social status. The subordinates usually adopt a higher pitch or breathy voice, while the dominators use a lower pitch or modal/creaky voice. In addition, CPP, F0, and H1-A3 are the key acoustic indicators to distinguish character voices. These results not only revealed the acoustic characteristics of character voices, but also guided dubbing vividly.